Impact of integrated reporting on enterprise value-based management: evidence from Ukraine - Fedir Zhuravka (Problems and Perspectives in Management, 2020)
An integrated approach to the enterprise value-based management (VBM) provides a precise assessment of all accounting entities. The implementation of such an approach allows determining the value of objects that do not have a material form (intangible assets), but have a significant impact on the enterprise value. The growing role of accounting data in enterprise value formation and management determines the necessity of the research. Thus, the article aims to investigate the effect of integrated reporting implementation on the VBM at the Ukrainian enterprises. Based on recent scientific researches, the study substantiates that the VBM approach should be based on an integrated reporting concept and proves the necessity of transition from the traditional accounting model to sustainability accounting in Ukraine. The findings reveal the approach of integrated reporting incorporation into the enterprise VBM system. The authors offer the concept of creating an integrated reporting model in Ukraine that considers economic and legal criteria, basic and qualitative principles, and production, human, financial, social, natural, and intellectual capital.